EFECTO DE UNA BACTERINA DE DOSIS ÚNICA CONTRA Mycoplasma hyopneumoniae SOBRE EL TÍTULO DE ANTICUERPOS, GANANCIA DE PESO Y LESIONES PULMONARES EN PORCINOS PROVENIENTES DE MADRES VACUNADAS - Pinto J., Chris (2012)
The aim of the present study was to determine whether the immunization with a single dose of a commercial bacterin against Mycoplasma hyopneumoniae influences antibody titles, bodyweight gain, and lung lesions in a commercial pig farm. Sixty piglets born from vaccinated sows were used. One group of 30 piglets (15males and 15 females) were vaccinated at 42 days of age and the other group remained unvaccinated, as a control group. Blood sampleswere collected at 21, 42, 70, 84, 112, and 145 days of age to determine antibody titleswith an Indirect ELISAtest.Animalswereweighed at 21 and 145 days of age and lung lesions were evaluated at slaughter (145 days). Nearly60% of pigs from both groups had high antibody titres at 21 days of age, but decreased by day 70. Titres increased between 84 and 145 days of age in the vaccinated group while increased by day 112 in the unvaccinated group. There were no significant differences in body weight gain between both groups. The 79.3 and 20.7% of piglets from the control group and the vaccinated group respectively, presented lung lesions. The results showed that vaccination with a single dose bacterin against M. hyopneumoniae increased antibody titles, although not in the entire population, and diminished the frequency of lung lesions, but no influenced body weight gain.